Unresponsive Thrombotic Thrombocytopenic Purpura (TTP): Challenges and Solutions - Lemiale V; Valade S; Mariotte E (Dove Medical Press, 2021)
Virginie Lemiale, Sandrine Valade, Eric Mariotte Medical Intensive Care Unit, Saint Louis University Hospital, Assistance Publique des Hôpitaux de Paris, Paris, FranceCorrespondence: Eric MariotteMedical Intensive Care Unit, Saint Louis University Hospital, Assistance Publique des Hôpitaux de Paris, 1 Avenue Claude Vellefaux, Paris, 75010, FranceEmail eric.mariotte@aphp.frAbstract: Thrombotic thrombocytopenic purpura (TTP) is a thrombotic microangiopathy secondary to a severely decreased A Disintegrin And Metalloprotease with ThromboSpondin type 1 repeats 13 (ADAMTS13) activity, resulting in the formation of widespread von Willebrand factor - and platelet-rich microthrombi. ADAMTS13 deficiency is mainly acquired through anti-ADAMTS13 autoantibodies in adults. With modern standards of care, unresponsive TTP has become rarer with a frequency of refractory/relapsing forms dropping from > 40% to < 10%. As patients with unresponsive TTP are at increased risk of mortality, prompt recognition and early therapeutic intensification are mandatory. Therapeutic options at the disposal of clinicians caring for patients with refractory TTP consist of increased ADAMTS13 supplementation, increased immunosuppression, and inhibition of von Willebrand factor adhesion to platelets. In this work, we focus on possible therapies for the management of patients with unresponsive TTP, and propose an algorithm for the management of these difficult cases.Keywords: thrombotic thrombocytopenic purpura, refractory, relapsing, rituximab, caplacizumab